Cellulose absorbable barrier for prevention of de-novo adhesion formation at the time of laparoscopic myomectomy: A systematic review and meta-analysis of randomized controlled trials. (February 2020) - Raimondo, Diego; Raffone, Antonio; Saccone, Gabriele; Travaglino, Antonio; Degli Esposti, Eugenia; Mastronardi, Manuela; Borghese, Giulia; Zullo, Fulvio; Seracchioli, Renato
Abstract: Objective: Myomectomy is the standard surgical treatment for symptomatic uterine leiomyomas, especially for patients wishing to preserve their fertility. However, this procedure is associated with adhesion formation. Several strategies have been proposed to reduce them. Cellulose absorbable barrier is widely used. We aimed to assess its effectiveness in the prevention of de-novo adhesion formation after laparoscopic myomectomy. Study design: A systematic review and meta-analysis was performed by searching electronic databases (i.e. MEDLINE, Scopus, ClinicalTrials.gov, EMBASE, Sciencedirect, the Cochrane Library at the CENTRAL Register of Controlled Trials, Scielo) from their inception until May 2019. We included all randomized clinical trials (RCT) comparing use of cellulose absorbable barrier (i.e. intervention group) with either placebo or no treatment (i.e. control group) in the prevention of de-novo adhesion formation at the time of laparoscopic myomectomy. Primary and secondary outcomes were defined before data extraction. The primary outcome was the incidence of adhesions at second-look laparoscopy. The secondary outcome was the operative time. Results: Three RCT, including 366 participants, were included. All trials evaluated women undergoing laparoscopic myomectomy who were randomized to intervention (either oxidized regenerated cellulose or carboxymethylcellulose powder adhesion barrier) or no treatment (control group). Women who received treatment had significantly lower incidence of adhesions at the second look laparoscopy (RR 0.63, 95 % CI 0.40–0.99). Interventions with use of cellulose absorbable barrier were 4 min longer (MD 4 min, 95 % CI 2.82–5.18). Conclusion: Use of cellulose absorbable barrier at the time of laparoscopic myomectomy reduces the risk of postoperative adhesions.